2006
DOI: 10.1016/j.ultramic.2006.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscope tip spontaneous retraction from dielectric surfaces under applied electrostatic potential

Abstract: Lyuksyutov, S. F.; Paramonov, P. B.; Mayevska, O. V.; Reagan, M. A.; Sancaktar, E.; Vaia, R. A.; and Juhl, S., "Atomic force microscope tip spontaneous retraction from dielectric surfaces under applied electrostatic potential" (2006 Abstract A time-resolved method for tip' retraction at ms-scale away from dielectric surfaces has been developed. Analysis of the forces in the system comprising AFM tip, water meniscus, and polymer film suggests that an electrostatic repulsion of the tip from the surface in the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In addition to previously proposed mechanism for tip repulsion, 20,21 we demonstrate that the meniscus impact force is another possible source for the enlargement of the tip-surface junction. We show that in fieldinduced meniscus formation, the meniscus can generate a hydrodynamic impact force large enough to overcome the electrostatic force acting on the tip.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…In addition to previously proposed mechanism for tip repulsion, 20,21 we demonstrate that the meniscus impact force is another possible source for the enlargement of the tip-surface junction. We show that in fieldinduced meniscus formation, the meniscus can generate a hydrodynamic impact force large enough to overcome the electrostatic force acting on the tip.…”
supporting
confidence: 68%
“…Several analytical models 12 such as sphere, single charge, and perfect cone models 13 have been proposed to quantify the force. 20 In their model, the tip and polymer substrate form a capacitor, and the observed tip deflection is due to the changing of the capacitor. Upon field application, the tip will be attracted to the surface by the electrostatic force, making the tip-surface distance smaller than the initial one without tip bias application.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…and that the properties of menisci depend on the field-induced polarization of the water layer adsorbed on the surface, the surface energy, and ambient water condensation from humid air 26 . A modeling of induced water condensation 27 , and free energy analysis of the system comprising of the tip, a water bridge, and a polymeric surface suggests water polarization due to the external electric field plays an essential role and affects tip dynamics 28 . Furthermore, it has been shown that the formation of a water meniscus in the proximity of an AFM tip is a major factor in electric charge transport 29 and generation of charge carriers 30 at the tip-surface junction.…”
Section: Stage I: Rearrangements In An Alkylthiolate Self-assembled Mmentioning
confidence: 99%
“…It has also been shown that nanometer-size menisci of organic liquids may sustain chemical reactions [7], and that the properties of menisci depend on the field-induced polarization of the water layer adsorbed on the surface, the surface energy, and ambient water condensation from humid air [8]. A modeling of induced water condensation [9], and free energy analysis of the system comprising of the tip, a water bridge, and a dielectric surface suggests water polarization due to the external electric field plays an essential and affects tip dynamics [10]. Furthermore, it has been shown that the formation of a water meniscus in the proximity of an AFM tip is a major factor in electric charge transport [11] and generation of charge carriers [12] at the tip-surface junction.…”
Section: Introductionmentioning
confidence: 99%